Knowledge as power criminal registration and community notification laws in America - Logan, Wayne A., 1960- (Stanford, Calif. : Stanford Law Books, 2009)
Societies have long sought security by identifying potentially dangerous individuals in their midst. America is no exception. This book traces the evolution of a modern technique - criminal registration laws. Registration, which originated in the 1930s as a means of monitoring gangsters, went largely unused for decades before experiencing a dramatic resurgence in the 1990s. Since then it has been complemented by community notification laws, which, like the 'Wanted' posters of the Frontier West, publicly disclose registrants' identifying information, involving entire communities in the criminal monitoring process.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal records -- United States; Law; United States of America, USA; Crime & criminology; Legal aspects of criminology; Laws of specific jurisdictions & specific areas of law; Criminal law: procedure & offences